The Anatomical Study and Clinical Significance of the Sinuvertebral Nerves at the Lumbar Levels. Issue 2 (15th January 2020) - Zhao, Qinghao; Cheng, Liang; Yan, Huibo; Deng, Shangxi; Zhao, Jianjun; Liu, Zezheng; Tan, Xuemei; Zhong, Enyi; Zhuo, Wentao; Jin, Dadi; Li, Qingchu
Abstract : Study Design: A dissection-based study of 10 embalmed human cadavers. Objective: The purpose of this study was to describe the sinuvertebral nerves at the lumbar level and to discuss their possible clinical significance. Summary of Background Data: Discogenic low-back pain is mediated by the sinuvertebral nerves. However, the detailed descriptions of the sinuvertebral nerves at the lumbar level are lacking. Methods: One hundred L1-L5 intervertebral foramina from 10 embalmed cadavers were studied. The presence of the sinuvertebral nerves was noted. The quantity, origin, pathway, innervation range, and spatial orientations of the sinuvertebral nerves in the L1-L5 intervertebral foramina were examined. Results: A total of 450 sinuvertebral nerves were identified in the 100 lumbar intervertebral foramina; sinuvertebral nerves were observed in 100.00% of the intervertebral foramina. The sinuvertebral nerves were routinely divided into the following two types: the sinuvertebral nerve deputy branch and sinuvertebral nerve main trunk. Three hundred twelve sinuvertebral nerve deputy branches were found; on average, there were approximately 3.12 (range, 1–8) branches in each intervertebral foramen. One hundred thirty-eight sinuvertebral nerve main trunks were found, and sinuvertebral nerve main trunks were observed in 97.00% of the intervertebral foramina. The initial portion of the sinuvertebral nerve was located along the posterior-lateral edge of the disc to the spinal canal. Sixty-one (44.20%) sinuvertebral nerve main trunks originated from the starting point of the gray ramus communicans of the nerve root; 77 (55.80%) sinuvertebral nerve main trunks originated from the anterior surface of the spinal ganglia of the nerve root. Conclusion: This is a systematic anatomy study that describes the sinuvertebral nerve at the lumbar level and may be of clinical importance to spinal surgeons. A comprehensive understanding of the distribution of sinuvertebral nerves may lead to significant benefits for patients undergoing percutaneous endoscopic treatment for discogenic low-back pain. Level of Evidence: 4 Abstract : One hundred lumbar intervertebral foramina from 10 cadavers were studied, and the existence and types of sinuvertebral nerves in the lumbar intervertebral foramina were described. Detailed anatomic studies of the sinuvertebral nerves in the lumbar intervertebral foramina were performed. The clinical significance of the sinuvertebral nerves was discussed.